Exploring therapy outcomes among HIV positive people who inject drugs (PWID) in Malaysia - Aida Roziana Ramlan (Kuliyyah of Pharmacy, International Islamic University Malaysia, 2021)
The role of Methadone Maintenance Therapy (MMT) with antiretroviral therapy (ART) initiation among HIV-positive people who inject drugs (PWID) is not widely studied in Malaysia. This study aims to compare the treatment outcomes and time to treatment (TTT) between HIV-positive PWID enrolled in the MMT program compared to those who were not. This retrospective study involves HIV infected PWID in Kuantan from the year of 2006 to 2019. The Kaplan Meier survival curve and the Cox proportional hazard model was used to compare the mortality rate and to measure the outcome. The TTT was calculated from the day of ART eligibility to ART initiation. A total of 141 PWID from 6 health clinics in Kuantan and Infectious Disease Clinic of Hospital Tengku Ampuan Afzan were included in this study. They were categorized into MMT only group (29 subjects), MMT + ART group (41 subjects), and ART only group (71 subjects). From the Kaplan Meier test, the 5-year cumulative survival probabilities were at 60.9% in the MMT only group, 94.1% in the MMT + ART group, and 98.5% in the ART only group. The cumulative mortality incidence was significantly different between MMT only group compared to MMT + ART group, and MMT only group compared to ART only group with p-value < 0.001 and 0.003. A total of 94 subjects had their viral load test available for both MMT + ART group (n=32) and ART only group (n=62). More than 95% of the subjects in the MMT + ART group (n=31) and ART only group (n=60) achieved good viral load suppression (defined as viral load <1000 copies/ml). Both groups showed good CD4 cells count recovery with increment of >50ccells/mm3 within 6 months. The time to treatment for ART only group was 2 months and 5.5 months in the MMT + ART group. The occurrence of opportunistic infection and low CD4 cells count baseline influenced earlier ART initiation in the ART only group. From the cox proportional hazard regression, the factors that reduced the mortality risk among PWID were the initiation of ART, HIV related counselling, and living with family with p value <0.05. The MMT program's 5-year cumulative retention probability for MMT + ART group compared to MMT only group was 93.6% and 41.2%. In conclusion, the initiation of ART improved PWID survival probability and clinical outcomes. Although the MMT program in this research was not associated with earlier ART initiation or a better outcome, it was evident that ART and MMT combination improved PWID retention in the healthcare system compared to PWID given MMT alone.